2008
DOI: 10.1186/1465-9921-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Could a defective epithelial sodium channel lead to bronchiectasis

Abstract: Our results suggest that several variants in ENaCbeta and gamma genes might be deleterious for ENaC function and lead to bronchiectasis, especially in patients who are trans-heterozygotes for ENaCbeta/CFTR mutations or variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
(40 reference statements)
1
29
1
1
Order By: Relevance
“…Fajac et al screened a group of 55 patients with diffuse idiopathic bronchiectasis (permanent dilation of the airways as a result of chronic bronchial infection) by sequencing SCNN1B and SCNN1G exons and identified five heterozygous missense variants (S82C, P369T, N288S in β, and G183S, E197K in γ subunit) in eight patients (Fajac et al, 2008). The S82C mutation was found in three unrelated patients who were also heterozygous for a CFTR mutation.…”
Section: Diseases Associated With Enac Mutationsmentioning
confidence: 99%
“…Fajac et al screened a group of 55 patients with diffuse idiopathic bronchiectasis (permanent dilation of the airways as a result of chronic bronchial infection) by sequencing SCNN1B and SCNN1G exons and identified five heterozygous missense variants (S82C, P369T, N288S in β, and G183S, E197K in γ subunit) in eight patients (Fajac et al, 2008). The S82C mutation was found in three unrelated patients who were also heterozygous for a CFTR mutation.…”
Section: Diseases Associated With Enac Mutationsmentioning
confidence: 99%
“…Abnormal ciliary motion will lead to recurrent infections due to retention of secretions. A more recent discovery of a congenital cause is that of Fajac et al ,20 who showed that some patients with idiopathic bronchiectasis carried a mutation in the ENaC β or γ genes, giving a defective epithelial sodium channel (ENaC) protein.…”
Section: Diagnosis Of Ncfbmentioning
confidence: 99%
“…To summarise the results from our 55 patients with bronchiectasis, 10 (18%) patients carried at least one missense mutation in the ENaC alpha (as outlined in this report), beta or gamma genes [1]. Among them, six had evidence of abnormal sodium transport, either in the sweat glands (sweat chloride concentration 40-59 mmol?L -1 ) or in the nasal epithelium (basal nasal potential difference (PD) magnitude .30 mV or ,10 mV).…”
Section: To the Editorsmentioning
confidence: 99%
“…The radiological features of a goitre include: heterogeneous attenuation, focal punctate or curvilinear calcification within the mass, rapid and prolonged enhancement of the mass after contrast injection, and continuity of the mass with one of the lobes of the thyroid gland [1].…”
Section: Diagnosis Of a Posterior Mediastinal Goitre Via Endobronchiamentioning
confidence: 99%
See 1 more Smart Citation